2020
DOI: 10.1590/0034-7167-2019-0403
|View full text |Cite
|
Sign up to set email alerts
|

Patients and informal caregivers’ questions about alveolar bone graft post-operative care

Abstract: Objectives: to identify patients’ and informal caregivers’ questions related to alveolar bone graft post-operative care. Methods: analytical and cross-sectional study, developed in a public and tertiary hospital between October 2017 and February 2018. The sample consisted of 46 participants. Data collection occurred during the preoperative nursing consultation through interview. The doubts were described in a form prepared by the researchers and later grouped by similarity of the subject. Results: doubts ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The grouping of doubts by similarity resulted in themes: food, care for the surgical wound, postoperative complications, period of convalescence, and medications. A similar result was observed in another investigation whose objective was to know patients' and caregivers' doubts about another orofacial surgery (18) .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The grouping of doubts by similarity resulted in themes: food, care for the surgical wound, postoperative complications, period of convalescence, and medications. A similar result was observed in another investigation whose objective was to know patients' and caregivers' doubts about another orofacial surgery (18) .…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that orthognathic surgery is a high-cost procedure. Thus, populations in need seek public institutions that offer the procedure for free, such as the hospital in which this research was conducted, which is managed entirely with public resources (15,18) . The grouping of doubts by similarity resulted in themes: food, care for the surgical wound, postoperative complications, period of convalescence, and medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 It is estimated that there is one case of a newborn with cleft lip and/or cleft palate for every 700 live births worldwide. 3 Meanwhile, in Brazil, it is one case for every 1,000. 2 Based on this, a study in Brazil with birth records between 2005 and 2016 identified that the South and Southeast regions had higher average rates when compared to other states, being 0.72 and 0.54 per 1,000 live births, respectively.…”
Section: Introductionmentioning
confidence: 99%